A Transplant‐Specific Quality Initiative–Introducing TransQIP: A Joint Effort of the ASTS and ACS. Issue 7 (20th May 2017) - Parekh, J.; Ko, C.; Lappin, J.; Greenstein, S.; Hirose, R.
Abstract : In an attempt to improve surgical quality in the field of transplantation, the American College of Surgeons (ACS) and American Society of Transplant Surgeons have initiated a national quality improvement program in transplantation. This transplant‐specific quality improvement program, called TransQIP, has been built from the ground up by transplant surgeons and captures detailed information on donor and recipient factors as well as transplant‐specific outcomes. It is built upon the existing ACS/National Surgical Quality Improvement Program infrastructure and is designed to capture 100% of liver and kidney transplants performed at participating sites. TransQIP has completed its alpha pilot and will embark upon its beta phase at approximately 30 centers in the spring of 2017. Going forward, we anticipate TransQIP will help satisfy Centers for Medicare and Medicaid Services requirements for a quality improvement program, surgeon requirements for maintenance of certification, and qualify as a clinical practice improvement activity under the Merit‐Based Incentive Payment System. Most importantly, we believe TransQIP will provide insight into surgical outcomes in transplantation that will allow the field to provide better care to our patients. Abstract : This article outlines the history, current efforts, and future plans of TransQIP, the first national surgical quality initiative in transplantation. See also "The AJT Report, "page 1697 .